Analysis of Internal and External Factors of Farmers that Influence the Productivity of Self-Help Palm Oil Plantations in Merlung District, West Tanjung Jabung Regency - Putri Humaira, Mutiara; Nainggolan, Saidin; Saputra, Ardhiyan (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aims to describe the conditions of self-help oil palm farming in Merlung District, West Tanjung Jabung Regency, and analyze the role of internal and external factors on productivity, including their influence through the moderating variable of production input use. Internal factors studied include age, education, farming experience, motivation, number of family members, and farmer ethnicity, while external factors include marketing access, FFB selling price, and access to the carrying market. The analysis was conducted using the Partial Least Square (PLS) method with a sample of 43 farmers. The results showed that oil palm farming is managed conventionally with an average land area of ​​2.6 ha per farmer. Maintenance activities include fertilization 1–4 times per year, spraying and pruning 1–2 times per year, and harvesting twice per month using family labor and outside labor. Internal factors were proven to have a positive and significant effect on productivity, while external factors did not have a direct effect. However, through moderation in the use of production inputs such as urea, NPK, and dolomite fertilizers, internal factors still have a positive, although not significant, influence, while external factors show a positive and significant influence on the productivity of self-help oil palm farming.